Evaluation of genetic resources of yellow passion fruit - de Freitas, Juan Paulo Xavier; de Oliveira, Eder Jorge; da Cruz Neto, Alírio José; dos Santos, Leandro Ribeiro (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to characterize and evaluate genetic resources of yellow passion fruit (Passiflora edulis) for its main economic traits. Agronomic evaluations were made and genetic parameters were estimated in 38 germplasm accessions from the passion fruit germplasm bank of Embrapa Mandioca e Fruticultura, using five controls from selections or genetically improved material. Two productive characteristics, three chemical qualities, and seven physical attributes of fruit were evaluated. An augmented block design with four replicates and ten plants per plot was used. The high coefficient of genetic variation, the index of variation greater than one, and the high heritability values indicate the existence of high genetic variability not yet explored, as well as favorable conditions to implement a breeding program. For most of the traits evaluated, accessions were superior to the controls. Accessions BGM185 and BGM051 are more promising for the fresh fruit market, due to fruit quality, while accessions BGM181, BGM034, BGM123, and BGM079 are recommended for the fruit juice industry, due to high productivity and pulp yield.